Serological description of neonatal umbilical cord blood from pregnant women confirmed with positive COVID-19 by RT-PCR at Rumah Sakit Umum Pusat H. Adam Malik, Medan, Indonesia - Benjamin Sihite; Makmur Sitepu; Khairani Sukatendel; Sarma Nursani Lumbanraja; Iman Helmi Effendi; Rizki Yaznil; Edy Ardiansyah (Universitas Airlangga, 2022)
HIGHLIGHTS 1. COVID-19 raises concern in regard with its effect on pregnancy.2. The serological descriptions of umbilical cord of neonates born from mothers suffering from COVID-19 were identified.3. Most of the serology was non-reactive IgG and IgM, followed was reactive IgG and the least was the reactive IgM. ABSTRACT Objective: To evaluate the serological description of the neonatal umbilical cord in COVID-19 mothers confirmed by RT-PCR at Rumah Sakit Umum Pusat (RSUP) H. Adam Malik Medan in January-June 2021. Materials and Methods: This study was an observational study with a case series approach where the cases were mothers infected with SARS CoV-2 confirmed by RT-PCR. The study was conducted at Universitas Sumatera Utara (USU) Hospital Laboratory and RSUP H. Adam Malik for 6 months, from January 2021 to June 2021. The data collected were analyzed using descriptive statistics. If the data were normally distributed, they were presented as mean + SD; otherwise, they were presented as median (min-max) for each variable. The Statistical Package for Social Sciences version 22.0 (IBM SPSS Corp.; Armonk, NY, USA) was used for statistical analysis. Results: Neonatal umbilical cord serology results (IgM and IgG) were predominantly non-reactive, where IgM was non-reactive in 43 neonates (97.7%) and IgG was non-reactive in 37 neonates (84.1%). In mothers without COVID-19 symptoms, neonate umbilical cord serology results were dominated by non-reactive IgM (88.6%) and IgG (79.5%). In mothers who recovered from COVID-19, neonate umbilical cord serology results were also dominated by non-reactive IgM (95.5%) and IgG (81.8%). Conclusion: The neonatal umbilical cord serology results from the mother confirmed with positive COVID-19 were nonreactive IgG and IgM in the majority of 35 (79%) samples, reactive IgG in 7 (15.9%), and reactive IgM in 1 (2%) sample.